2010
DOI: 10.4103/0377-4929.59193
|View full text |Cite
|
Sign up to set email alerts
|

Morphological findings in bone marrow biopsy and aspirate smears of visceral kala azar: A review

Abstract: Hyper cellular marrow, increased lymphocytes and plasma cells, marrow granulomas, hemophagocytosis, myelofibrosis, myelodysplasia and gelatinous transformation of the marrow were notable features the presence of which together or individually should caution a pathologist to search for Leishman Donovan (LD) bodies in patients especially in a non-endemic zone in a tropical country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 2 publications
3
21
0
1
Order By: Relevance
“…Kalazar is one of the cause of pancytopenia and frequency is very high in some studies done in india and Pakistan. 15 Visceral leishmaniasis is endemic in some parts of india and may simulate and cause many hematological disorders like pancytopenia, myelofibrosis, MDS and hemophagocytosis as mentioned by Sud et al 16 In this study one case of Gaucher disease was diagnosed in a 20 yrs female. Study of Ahmad et al showed that storage disorders were diagnosed in 2.4% cases of pancytopenia.…”
Section: Figure 6: Acute Myeloblastic Leukemia Myeloblasts With Finementioning
confidence: 99%
“…Kalazar is one of the cause of pancytopenia and frequency is very high in some studies done in india and Pakistan. 15 Visceral leishmaniasis is endemic in some parts of india and may simulate and cause many hematological disorders like pancytopenia, myelofibrosis, MDS and hemophagocytosis as mentioned by Sud et al 16 In this study one case of Gaucher disease was diagnosed in a 20 yrs female. Study of Ahmad et al showed that storage disorders were diagnosed in 2.4% cases of pancytopenia.…”
Section: Figure 6: Acute Myeloblastic Leukemia Myeloblasts With Finementioning
confidence: 99%
“…In Ethiopia Visceral Leishmaniasis has been reported from at least 40 areas, with the most endemic areas are Metema and Humera lowlands of Northwest, which accounts for 60% of the total burden [17]. The disease is characterized by fever, hepatosplenomegaly, anemia, leucopenia and Thrombocytopenia [8].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Hematological abnormalities are common complication of patients having Visceral Leishmaniasis since the disease is a chronic illness which is characterized by irregular fever, hepatosplenomegaly and panctyopenia, progressive weakness and emaction which can result to death if left untreated [8]. In addition, the spleen size and duration of illness correlate with some of the main hematological features [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations